2022
DOI: 10.3390/agronomy12040797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Conventional Cereal Production Methods on Fusarium Head Blight and Mycotoxin Contamination Levels

Abstract: Fusarium mycotoxins in cereals constitute major problems for animal and human health worldwide. A range of plant pathogenic Fusarium species that can infect cereal plants in the field are considered the most important source of mycotoxins, such as deoxynivalenol (DON), zearalenone (ZEA), T-2 toxin, and HT-2 toxin, in small-grain cereal crops in temperate climates. In this article, we (i) critically review the available knowledge on the impact of contrasting production systems (organic versus conventional) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 111 publications
6
42
0
Order By: Relevance
“…This crop is directly related to food security and the global economy [3]. However, root rot caused by Fusarium culmorum and Fusarium avenaceum, head blight (FHB) caused by Fusarium graminearum, snow mold caused by Microdochium nivale and Fusarium nival, and powdery mildew caused by Blumeria graminis are the most widespread and harmful wheat diseases worldwide [4][5][6]. Consequently, these fungal diseases can cause colossal yield losses of up to 20% of total wheat production if an efficient plant protection system is not established [7].…”
Section: Introductionmentioning
confidence: 99%
“…This crop is directly related to food security and the global economy [3]. However, root rot caused by Fusarium culmorum and Fusarium avenaceum, head blight (FHB) caused by Fusarium graminearum, snow mold caused by Microdochium nivale and Fusarium nival, and powdery mildew caused by Blumeria graminis are the most widespread and harmful wheat diseases worldwide [4][5][6]. Consequently, these fungal diseases can cause colossal yield losses of up to 20% of total wheat production if an efficient plant protection system is not established [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Northern Europe the severity of lodging and biotrophic diseases such as mildew and rust in manure-fertilized organic crops was (i) significantly lower than in mineral NPK-fertilized crops grown without fungicide/growth regulator treatment and (ii) below the threshold at which fungicide/growth regulator applications would become economically viable in conventional farming [ 4 , 6 , 7 ]. In addition, a recent literature review by Bernhoft et al [ 51 ] concluded that, overall, the risk of Fusarium head blight and mycotoxin contamination of wheat grain is lower in organic compared with conventional production systems. They describe a range of agronomic factors linked to an increased risk of Fusarium infection and mycotoxin levels in conventional production.…”
Section: Agronomic Protocols Used In Organic and Conventional Wheat P...mentioning
confidence: 99%
“…They describe a range of agronomic factors linked to an increased risk of Fusarium infection and mycotoxin levels in conventional production. Interestingly, risk factors in conventional systems include (i) minimum tillage, (ii) short rotations, especially growing wheat after wheat or maize, (iii) high N fertilizer inputs, and (iv) the use of certain types of fungicide (e.g., strobilurins) and the growth regulator chlormequat, which is used to reduce stem length and the risk of lodging in wheat [ 51 ].…”
Section: Agronomic Protocols Used In Organic and Conventional Wheat P...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by spores morphologically similar to Fusarium poae, with a similar mycotoxin profile to Fusarium sporotrichioides [ 3 ]. The occurrence of Fusarium langsethiae and its mycotoxins in a wide range of cereals and cereal products such as oats, wheat, and barley has been extensively examined [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%